Role of intermolecular interactions and conformational changes in the polymorphism and vitrification process of 2, 2′′-bis-substituted para-terphenyls. Issue 18 (22nd April 2020) - Nowok, Andrzej; Kuś, Piotr; Dulski, Mateusz; Kusz, Joachim; Książek, Maria; Zubko, Maciej; Szeremeta, Anna Z.; Pawlus, Sebastian
Abstract : Conformational diversity of 2, 2′′-bis-substituted para -terphenyls leads to polymorphism and contributes to their unique vitrification abilities. Abstract : In the past decades, para -terphenyls have been attracting tremendous attention due to their polymorphism and conformational diversity. In this work we report the synthesis, crystal structure, polymorphism and dielectric properties of two 2, 2′′-bis-substituted para -terphenyls: 2, 2′′-bis(hydroxymethyl)- para -terphenyl and 2, 2′′-bis(acetyloxymethyl)- para -terphenyl. On the basis of calorimetric and X-ray studies, we showed that the latter compound occurs in at least four polymorphic forms with melting points equal to 364, 345, 341 and 326 K, differentiated also in terms of thermodynamic stability and crystal symmetry. The most stable polymorph I is characterized by the P 21 / n space group. 2, 2′′-Bis(hydroxymethyl)- para -terphenyl crystallizes in the monoclinic P 21 / c space group. Both 2, 2′′-bis-substituted para -terphenyls can undergo vitrification, which is a highly exceptional feature for this class of chemical compounds and has not been reported before. Consequently, the molecular dynamics and conformational changes in the glassy and supercooled liquid states were analyzed by means of IR and broadband dielectric spectroscopy. Two relaxation processes were observed for both compounds: structural α-relaxation, connected with reorientational motions of molecules in supercooled liquid, and intermolecular γ-relaxation, ascribed to rotational motions of substituents of the para -terphenyl skeleton. Taking into account the ongoing discussion about the conformational diversity of the para -terphenyl skeleton, we showed that although free rotation of benzene rings is suppressed, the molecules in the glassy and liquid states can adopt both twisted and helical conformations, which results in diversity of the polymorphic forms.